2013
DOI: 10.5301/ejo.5000297
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Retinal Vasculopathy Associated with Autosomal Dominant Dyskeratosis Congenita

Abstract: Purpose To report a case of autosomal dominant dyskeratosis congenita (AD-DC) complicated by bilateral retinal vasculopathy and proliferative retinopathy with vitreous hemorrhage in the right eye, in the absence of pancytopenia. Methods We report a 32-year-old woman who presented with floaters in her right eye. She underwent complete ophthalmic examination and fundus fluorescein angiography. Results Funduscopic examination revealed vascular sheathing in the temporal periphery of both eyes and a vitreous he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 7 publications
(21 reference statements)
0
20
0
1
Order By: Relevance
“…6-9 A recent study that included 28 patients with DC found three of the patients had retinal vascular abnormalities, which included neovascularization, exudative retinopathy, and retinal detachment, 10 suggesting that retinopathy, although infrequent, is present in a significant minority of DC patients. Because retinopathy has been reported in autosomal dominant forms of DC, which can present later in life and with subtle systemic findings, 6,7 a high index of suspicion may be required to make the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…6-9 A recent study that included 28 patients with DC found three of the patients had retinal vascular abnormalities, which included neovascularization, exudative retinopathy, and retinal detachment, 10 suggesting that retinopathy, although infrequent, is present in a significant minority of DC patients. Because retinopathy has been reported in autosomal dominant forms of DC, which can present later in life and with subtle systemic findings, 6,7 a high index of suspicion may be required to make the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Retinal abnormalities are rare, 4 and have been reported in forms of hemorrhages, neovascularization, arteriosclerosis, retinal vascular sheathing, macular edema, preretinal fibrosis, nerve fiber layer infarction, and optic atrophy. 58 However, the vascular sheathing in the previously published description were mild and peripheral. 4,5 We encountered a boy who presented frosted branch angiitis (FBA) after recovery of mycoplasma pneumonia.…”
Section: Introductionmentioning
confidence: 78%
“…58 However, the vascular sheathing in the previously published description were mild and peripheral. 4,5 We encountered a boy who presented frosted branch angiitis (FBA) after recovery of mycoplasma pneumonia. To our knowledge, this is the first report of FBA in children with DC.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…47 Only a small proportion of patients with dyskeratosis congenita had retinal vascular changes; however, early recognition and treatment of these changes can prevent retinal neovascularization, exudative retinopathy, and retinal detachment and, therefore, the related vision loss. 48,49 In addition to the syndromic manifestations, treatment of dyskeratosis congenitia with radiation or the use of steroids before stem cell transplantation will increase the risk of glaucoma and cataract formation. A baseline ophthalmologic exam and periodic eye exams are therefore recommended for every patient with dyskeratosis congenita.…”
Section: Ocular Manifestationsmentioning
confidence: 99%